2007
DOI: 10.1073/pnas.0610731104
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-155 is induced during the macrophage inflammatory response

Abstract: The mammalian inflammatory response to infection involves the induction of several hundred genes, a process that must be carefully regulated to achieve pathogen clearance and prevent the consequences of unregulated expression, such as cancer. Recently, microRNAs (miRNAs) have emerged as a class of gene expression regulators that has also been linked to cancer. However, the relationship between inflammation, innate immunity, and miRNA expression is just beginning to be explored. In the present study, we use mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

75
1,475
4
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 1,679 publications
(1,560 citation statements)
references
References 47 publications
75
1,475
4
6
Order By: Relevance
“…We demonstrated that IFN-␣/␤ treatment of monocytes induced the expression of anti-HIV miRNAs ( Figure 2C). This finding supports the studies by others 36,43,44 showing that IFN-␣/␤ is the potent inducer of miRNAs in several cell systems. However, this IFN-mediated anti-HIV innate immunity in monocytes was dampened by morphine treatment (Figure 2C).…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated that IFN-␣/␤ treatment of monocytes induced the expression of anti-HIV miRNAs ( Figure 2C). This finding supports the studies by others 36,43,44 showing that IFN-␣/␤ is the potent inducer of miRNAs in several cell systems. However, this IFN-mediated anti-HIV innate immunity in monocytes was dampened by morphine treatment (Figure 2C).…”
Section: Discussionsupporting
confidence: 92%
“…Murine macrophages up-regulate miR-155 after exposure to poly(I-C) and TNF␣ (38), whereas human monocytes increase miR-146a after LPS stimulation (29). We found increased levels of miR-155 in monocytes derived from the synovial fluid of RA patients as compared with those derived from the RA peripheral blood.…”
Section: Discussionmentioning
confidence: 62%
“…This adds to the growing evidence of the role of MAP kinases and their downstream transcription factor targets in the regulation of miR (O'Connell et al, 2007;Rahadiani et al, 2008). In addition, BCR activation induces miR-155 through ERK and JNK but not p38 activation through a conserved AP-1 element .…”
Section: Ebv Lmp1 Regulates Tcl1 Through Mir-29bmentioning
confidence: 70%